Curatopia 2019
DOI: 10.7228/manchester/9781526118196.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement, Indigenous heritage and the complex figure of the curator: foe, facilitator, friend or forsaken?

Abstract: Curation is increasingly recognised as a profession of high standing which requires extensive higher education. However, the proliferation of community engagement since the 1980s has placed new pressures and expectations on curators, thus complicating their role. This is particularly evident in the case of ethnographic curators working with indigenous communities. This chapter explores these issues by considering the ways that working with Blackfoot First Nations communities have affected the role and work of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…160–161). In the UK, the decline in the number of curators in museums has led to concerns from the curator community on the need to raise public awareness on the important role of curatorial knowledge in museum activities and the communities they serve (Ewin & Ewin, 2016, Onciul, 2019, pp. 168–169; also Deuchar, 2016).…”
Section: From Connoisseur To Brokermentioning
confidence: 99%
See 1 more Smart Citation
“…160–161). In the UK, the decline in the number of curators in museums has led to concerns from the curator community on the need to raise public awareness on the important role of curatorial knowledge in museum activities and the communities they serve (Ewin & Ewin, 2016, Onciul, 2019, pp. 168–169; also Deuchar, 2016).…”
Section: From Connoisseur To Brokermentioning
confidence: 99%
“…160-161). In the UK, the decline in the number of curators in museums has led to concerns from the curator community on the need to raise public awareness on the important role of curatorial knowledge in museum activities and the communities they serve (Ewin & Ewin, 2016, Onciul, 2019also Deuchar, 2016). In France, curators, or conservateurs du patrimoine, recently voiced their concerns about the future of state-legislated curatorship, denouncing greater administrative control and financial and personnel shortages, all to the detriment of curators who, they felt, were in a fragile and steep decline (Le livre blanc des mus ees de France, 2011).…”
Section: From Connoisseur To Brokermentioning
confidence: 99%
“…While the rise in participatory approaches is causing scholars to declare a shift in the role of the heritage professional from one of subject expert to expert mediator or facilitator (cf. Thomas 2004, Proctor 2010, Onciul 2019, research into perceptions of expertise tells a more complicated story, as several of the sources cited above also recognise. A survey conducted for the Profusion theme of the Heritage Futures research programme recently found that staff involved in collections development decisions in social history collections in the UK were divided on whether they felt members of the public should be involved in collecting and disposal decisions.…”
Section: Expertisementioning
confidence: 99%
“…During the colonial period, museum curators were endowed with tremendous authority in configuring ethnographic objects thereby othering Indigenous knowledge systems. However, in the decolonial turn, the curator is no longer a lone expert and a voice of authority but rather a facilitator of community engagement and collaboration (McCarthy, Hakiwai, & Schorch, 2019; Onciul, 2019). Collaborations have therefore transformed ethnographic museums from being places that were once regarded as displaying ‘others’ to locations of cultural revitalisation, community voice and empowerment (Onciul, 2019, 160) (Figure 1).…”
Section: Colonial Classifications In the Old Beit Gallerymentioning
confidence: 99%
“…In this regard, it can be further posited that museums especially in Africa are being challenged to give up on their authoritarian voice of control to allow communities to speak for themselves. Accepting source communities as experts and research partners can change the museum practice by opening up different ways of knowing and caring for the past (Onciul, 2019). Curatorship has thus evolved from being a strict specialised connoisseurship of individuals to a public service that attend to problems in contemporary communities (Schorch et al, 2019).…”
Section: Co‐curation As a Decolonised Exhibitory Strategymentioning
confidence: 99%